Devizaárfolyam modellezés nemkonvencionális monetáris politika vitele mellett az európai jegybankok sajátosságai - Mészáros Mercédesz (2019)
Following the latest subprime crisis, central banks introduced several unconventional instruments which had spillover effects on foreign exchange rates. The aim of this paper was to explore whether the use of ZLB and these unconventional instruments had an impact on the changes in foreign exchange rates. By running dynamic panel regressions, I analyzed this in on a sample of 6 European central banks. Based on my results, unconventional monetary policy had a significant impact on the exchange rate fluctuations in the short term, even with the use of instruments where there was no targeted exchange rate regulation, such as QE and liquidity-providing loan programs.